Transitions of smectic A to tilted phases in thin free standing films of liquid crystal - Lum, Chia Yuee; Ong, Lye Hock; Mojca Cepic, (Universiti Kebangsaan Malaysia, 2011)
The transition of orthogonal smectic A (SmA) phase to the tilted phases, upon lowering the temperature, is explored with a discrete phenomenological model and the phase diagrams are presented. The results show that the transition of SmA to uniplanar structures can be affected by the effect of chirality. The areas showing the uniplanar phase in the phase diagrams diminish with the increase in effect of chirality